Sura Magadha: Patriotisme Dan Nasionalisme Warga Banjar Dalam Perang Banjar Tahun 1868 - Ida Bagus Wika Krishna (Pramana: Jurnal Hasil Penelitian, 2021)
This article discusses the conflict between the people of North Bali and the Dutch colonialism, especially in Banjar Village, which was known as the Banjar War which took place in 1868. The Balinese resistance war that broke out in various areas became known as puputan, which in a dictionary means finish and refers to the meaning that in war, self-respect must include everything, including body and soul. The main cause of this opposition started when the Dutch lowered and replaced the Banjar retainer Ida Made Rai. This research was conducted using historical methods, including heuristics, criticism, synthesis and historiography. The results of this study found that the resistance was motivated by Dutch politics and intervention to colonize the total area of Bali, especially Buleleng and Banjar Villages. This decision has a logical crisis from the critical attitude of the Banjar people with the crisis situation at that time. The uniqueness of this prohibition is the critical attitude and methods of clashing as a last resort in their war which gave birth to the ideology of Sura Magadha.